Conveyor Damage in Coal Transhipment Activities at PT. Pelindo II Cabang Teluk Bayur - Satria, Iman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The aim of this research is to determine the impact that occurs on conveyor damage during coal transshipment activities and to find out what efforts are being made and to overcome the impact of damage at PT. Pelindo Teluk Bayur. This study used descriptive qualitative method. Data was collected through interviews, observation, literature study and documentation. The results of the research show the impact that occurred on conveyor damage during coal transshipment activities at PT. Pelindo Teluk Bayur, namely all loading activities at the jetty stopped, then the transshipment activity process at Teluk Bayur was hampered, and demurrage was given by the buyer to PT. Pelindo Teluk Bayur. Efforts to reduce the impact of damage to the conveyor at the TCM jetty on coal transhipment activities in Muara Berau anchorage at PT. Pelindo Teluk Bayur is by speeding up conveyor repairs at the TCM jetty, diverting several barges that have arrived at the TCM jetty area to other jetty areas, changing vessel schedules so that there is no accumulation of vessels at Teluk Bayur and speeding up the loading of coal into vessels with the aim of not prolonging demurrage given.